1996
DOI: 10.1021/bi9615001
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and Conformational Dynamics of Escherichia coli Ribosomal Protein L7/L12

Abstract: Fluorescence methods were utilized to study dynamic aspects of the 24 kDa dimeric Escherichia coli ribosomal protein L7/L12. Oligonucleotide site-directed mutagenesis was used to introduce cysteine residues at specific locations along the peptide chain, in both the C-terminal and N-terminal domains, and various sulfhydryl reactive fluorescence probes (iodoacetamido) fluorescein, IAEDANS, pyrenemethyl iodoacetate) were attached to these residues. In addition to the full-length proteins, a hinge-deleted variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 45 publications
3
48
0
Order By: Relevance
“…Using the Pemn equation and the observed polarization of 0.33 (Fig. 1) for mMDH-FITC conjugates prepared using protocol P, a Po value for fluorescein of 0.47 (Hamman et al, 1996) and the observed lifetime of 4.16 ns, the calculated rotational relaxation time calculated is 25 ns. The Debye rotational relaxation time expected for a rigid, spherical 68 kDa protein, in aqueous buffer at 20 "C (77 = 1 .OO cp), assuming a partial specific volume of 0.75 mL/g [calculated from the amino acid sequence (Birktoft et al, 1982) using the method of Cohn and Edsall (1943)] and a hydration of 0.22 mL/g, is 74 ns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Pemn equation and the observed polarization of 0.33 (Fig. 1) for mMDH-FITC conjugates prepared using protocol P, a Po value for fluorescein of 0.47 (Hamman et al, 1996) and the observed lifetime of 4.16 ns, the calculated rotational relaxation time calculated is 25 ns. The Debye rotational relaxation time expected for a rigid, spherical 68 kDa protein, in aqueous buffer at 20 "C (77 = 1 .OO cp), assuming a partial specific volume of 0.75 mL/g [calculated from the amino acid sequence (Birktoft et al, 1982) using the method of Cohn and Edsall (1943)] and a hydration of 0.22 mL/g, is 74 ns.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, ''local'' motion was attributed to mobility of a probe in excess of that expected by the rotation of a rigid body to which it is attached, due to probe motion around its point of attachment to the macromolecule (Wahl & Weber, 1967). Eventually, however, improved methodologies and a better understanding of the dynamic nature of proteins led to the appreciation that ''local'' motion could include internal or domain motions of the protein as well, such as the segmental flexibility attributed to antibodies (Reidler et al, 1982: Oi et al, 1984Hamman et al, 1996). Hones et al (1986), using NADH as the bound fluorophore, reported a rotational correlation time (4) of 27 ns for mMDH at 25 "C, which corresponds to a Debye rotational relaxation time of 81 ns ( p = 34; Jameson & Sawyer, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal domains can be cross-linked to each other in different orientations yet retain full functional activity in supporting polypeptide synthesis (12). Flexibility of L7/L12 has been demonstrated in solution by fluorescence techniques (13) and in the ribosome by proton NMR (14, 15), by electron microscopy (16), and with fluorescence probes attached to the C-terminal domains (13,17,18).Immunoelectron microscopy with monoclonal antibodies (19) directly showed the presence of the C-terminal domain at the tip of the stalk and the N-terminal domain at the base of the stalk. This was consistent with earlier demonstrations that the N-terminal domain was responsible for binding of the fulllength L7/L12 to L10 and to the ribosome (9, 10).…”
mentioning
confidence: 99%
“…The C-terminal domains can be cross-linked to each other in different orientations yet retain full functional activity in supporting polypeptide synthesis (12). Flexibility of L7/L12 has been demonstrated in solution by fluorescence techniques (13) and in the ribosome by proton NMR (14, 15), by electron microscopy (16), and with fluorescence probes attached to the C-terminal domains (13,17,18).…”
mentioning
confidence: 99%
“…The latter implication first was questioned when L7͞L12 variants with C-terminal domains cross-linked in different disparate orientations that precluded the formation of the conserved surface were constructed and found to be active (11). Moreover, the C-terminal domains are separated from each other by an average of 85 Å (12) and are independently mobile (13). The results imply that a preferred close orientation of C-terminal domains relative to each other is not important for L7͞L12 activity, nor is it likely that two heads function while associated with each other.…”
mentioning
confidence: 99%